A study of the effects of olfactory stimulus duration and concentration on sleep arousal under fatigue driving - Huo, Faren; Lu, Yingfan; Fang, Fei; Liu, Xuanhui (Frontiers in Psychology, 2025)
Olfactory stimulation can alleviate passive task-related fatigue (PTR), but its mechanism and influencing factors are still unclear. This study used a controlled experimental design to explore the effect of mint odor on driving fatigue by comparing the driving fatigue induction stage (monotonous driving) with the awakening stage (olfactory intervention). The experiment controlled the stimulation duration (1 min vs. 8 min), traffic flow (low vs. high), and concentration (low, medium, and high), and combined subjective scales, heart rate variability (HRV), and percent eyelid closure (PERCLOS) indicators to evaluate the effect. The results showed that under high traffic flow, 8 min of stimulation relieved fatigue most significantly; moderate concentration was the best for physiological arousal, but high concentration was subjectively preferred; HRV was more sensitive than PERCLOS, and age and driving experience regulated the response. Context-based olfactory intervention can effectively alleviate fatigue, and stimulation duration and environmental load are key regulatory factors. This study advances the theoretical framework of multimodal fatigue management and provides practical suggestions for the design of adaptive vehicle warning systems.